LÃ¢â¬â¢ANALYSE SEMIOTIQUE DE LA NOUVELLE LES YEUX DE SOIE DE FRANÃâ¡OISE SAGAN (SEMIOTIC ANALYSE IN FRANÃâ¡OISE SAGANÃ¢â¬â¢S THE EYES OF SILK) - Syaefudin, Mohamad (Language Circle: Journal of Language and Literature, 2011)
This writing aims to reveal that behind womenÃ¢â¬â¢s weakness and tenderness there is an invisible power that can overturn menÃ¢â¬â¢s domination. While care seems more effective to get womenÃ¢â¬â¢s love and respect, men tend to rely on domination. This, in fact, does not always work. Semiotic is a kind of analysis used to uncover the meaning of signs in a text. In literature this analysis serves to show different types of meaning. In this novel, there is a couple - Jerome and Monica, and their friend - Stanislas. Jerome dominates and excels in everything. He spends time hunting wild animals and doing manÃ¢â¬â¢s other sports. Monica is a housewife who is thirsty of her husbandÃ¢â¬â¢s attention. She makes an affair with Stanislas, her husbandÃ¢â¬â¢s friend. One day Jerome takes Monica, Stanislas and another woman to deer-hunting. Later he finds out that there is something between her wife and Stanislas. Driven by jealousy, he decides to kill them both. The writer used semiotic analysis because there are many signs of syntagmatic and paradigmatic meanings to discover. Key words: sÃÂ©miotique, littÃÂ©rature